Economic report of the president : transmitted to the congress January, 1989 - United States President; Council of Economic Advisers (Washington: United States Government Printing Office, 1989)
This the Economic Report of the President transmitted to the congress January, 1989 by Ronald Regan, together with the annual report of the Council of Economic Advisers.
together with the annual report of the Council of Economic Advisers.
rpm 13/06/2017
Loans
Keywords: United States -- Economic policy; United States -- Economic conditions; Economic history; Economic policy; Unites States